A methodological approach to sugar mill diversification and conversion (2012)
Sugar industry diversification is complex, being constrained by biophysical and socioeconomic conditions. Ongoing work has shown the sugarcane industry’s potential as biorefinery or its sustainable use by offering products as raw material. However, few studies have studied how such potential could be achieved by promoting a conventional sugar mill through integrating its indicators for developing an efficient diversified processing plant which would contribute towards fossil energy saving and competitiveness. This paper presents a conceptual framework for analysis based on existing knowledge regarding sugar industry state-of-the-art for evaluating diversification, using analytical hierarchy process (AHP) as a tool for analysing complex systems, identifying alternatives to the current situation and discussing them to facilitate collective decision-making. Sugar mill AHP scores enabled discussion about the variables most affecting sugar mill diversification (0.332 factory yield, 0.327 sugar mill products and 0.121 sugarcane quality). The results serve as a useful guidance for formulating strategies for the optimum use of by-products in a sugar mill while maximising benefits to modify/convert a traditional sugar mill to a so-called bio-refinery.